STRATEGI PEMASARAN IKAN MAS DI DESA SITU DAUN, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Kurniawan, Afan Tri; Anggarawati, Sari; Suwarnata, Anak Agung Eka (Agrisintech (Journal of Agribusiness and Agrotechnology), 2022)
ABSTRACTRana Berkah Jaya is a company that produces fresh carp in Tenjolaya, Bogor Regency. Carp has a promising market opportunity both as a Sundanese food and for fishing ponds. These opportunities lead to increasingly fierce business competition. For this reason, it is necessary to study internal and external factors and develop a marketing strategy using IFAS, EFAS and SWOT analysis. Internal strengths factor are products with guaranteed quality; competitive prices; payment method; services; various sizes of fish. Weakness factors are: the number of products is limited; promotional technology; pond quality; water sources. External factors that are opportunities are: potential market; regular customer; many fishing ponds; lack of jumbo cultivators. while the threat factors are: similar fishery business; fish feed costs; pests and diseases; climate disturbance. Furthermore, a SWOT analysis show several alternative marketing strategies were obtained consisting of the SO strategy: maintaining various sizes for fishing pool needs; keep cheap price in order to be competitive; service optimizing to consumers. ST strategy is to improve product quality; improve product quality with better maintenance techniques. The WO strategy is to utilize social media technology for promotion; Forming business partners to maintain product continuity. The WT strategy is to utilize cultivation technology to minimize climate disturbances and looking for alternative water sources to avoid pests and diseases.Â ABSTRAKRana Berkah Jaya merupakan salah satu perusahaan yang memproduksi ikan mas segar di Tenjolaya Kabupaten Bogor. Ikan mas memiliki potensi pasar cukup menjanjikan baik sebagai makanan khas Sunda maupun untuk kolam pemancingan. Peluang tersebut menimbulkan persaingan usaha yang ketat. Untuk itu perlu dilakukan kajian faktor internal dan eksternal serta menyusun startegi pemasarannya menggunakan analisis IFAS, EFAS dan SWOT. Faktor internal yang merupakan kekuatan adalah kualitas produk; harga produk; cara pembayaran; jasa pelayanan; ukuran ikan. Sedangkan faktor kelemahannya adalah: jumlah produk terbatas; teknologi promosi; kondisi kolam; sumber air. Faktor eksternal yang merupakan peluang adalah: potensi pasar; pelanggan tetap; jumlah kolam pemancingan; minimnya pembudidaya jumbo. Faktor ancamannya adalah: usaha sejenis; biaya pakan; hama dan penyakit; gangguan iklim. Analisis SWOT menunjukkan beberapa pilihan strategi pemasaran di antaranya strategi SO yaitu mempertahankan ukuran ikan yang bervariasi agar bisa masuk ke tempat pemancingan; memepertahankan harga murah agar berdaya saing; meningkatkan pelayanan kepada konsumen agar kembali berbelanja. Strategi ST yaitu meningkatkan kualitas produk; menjaga kualiatas produk dengan memperhatikan teknik pemeliharaan. Strategi WO yaitu memanfaatkan teknologi media sosial untuk promosi; membentuk mitra usaha untuk menjaga kontinuitas produk. Strategi WT yaitu memanfaatkan teknologi budidaya untuk meminimalisir gangguan iklim; mencari alternatif sumber air untuk menghindari hama dan penyakit.Â